Report on a transborder spread of carbapenemase-producing bacteria by a patient injured during Euromaidan, Ukraine. (November 2015) - Hrabák, J.; Študentová, V.; Adámková, V.; Šemberová, L.; Kabelíková, P.; Hedlová, D.; Čurdová, M.; Zemlickova, H.; Papagiannitsis, C.C.
Abstract: Spread of carbapenemase-producing bacteria has been described all over the world. This phenomenon may be accelerated by many factors, including wars and natural disasters. In this report, we described an NDM-1-producing Klebsiella pneumonia ST11 recovered from a patient injured during the Maidan revolution in Ukraine. To our knowledge, this is the first report of a carbapenemase-producing Enterobacteriaceae in Ukraine and one of several reports describing wound colonization/infection of humans injured during war.